Comparative analysis of the dimensioning of the steel area of shoes between the cypecad software and the manual calculation using the strut method (Research, Society and Development, 2023)
The evolution of structural analysis systems made it possible to end the need to optimize the geometric dimensioning of foundation components, with this, the use of software occurs not only for saving time, but also for the satisfactory level of precision in obtaining results and details. , favoring productivity in structural projects. The foundation, also known as infrastructure, is an element that is located below the ground, whose function is to support and transport the loads received from the structure to the ground in a safe and effective way. Therefore, the objective of this work is to compare the design of an isolated footing type foundation, using the cypecad software and the strut method. In this way, it was found that in the design carried out by Cypecad, in all cases of loads on the shoes, there was a superior design compared to the manual design, a result that should oversize the structure and also, variations in the amounts of steel and also in the dimensions of the footings can occur due to rounding made in the calculations.